PENGEMBANGAN STANDAR PROSEDUR OPERASIONAL (SPO) UNTUK PELAYANAN KEGAWATDARURATAN OBSTETRI - Ria Lusi Utami; Winda Febriani; Nita Berliana Br Ginting (Jurnal Minfo Polgan, 2024)
Obstetric emergencies are a leading cause of maternal and neonatal morbidity and mortality worldwide. Prompt, appropriate, and standardized care is crucial to saving lives. Standard Operating Procedures (SOPs) are documents that guide the steps in a process, ensuring consistency, efficiency, and safety. This literature review aims to explore the importance, principles, and challenges in developing and implementing SOPs for obstetric emergency care. The review results indicate that clear, concise, and evidence-based SOPs significantly improve response speed, adherence to clinical protocols, team coordination, and ultimately, clinical outcomes for mothers and babies. Effective SOP implementation can reduce variation in practice, minimize medical errors, and empower healthcare workers in crisis situations. Challenges include the need for socialization and training, ongoing updates, and resistance to standardization. Developing effective SOPs requires a participatory approach, leadership commitment, and integration with broader quality management systems.